Practical training report: Sarawak Chief Minister Department / Noor Fadziela Iswandy - Iswandy, Noor Fadziela (University Technology MARA Sarawak, 2012)
Sarawak’s State Legislative Assembly, the oldest legislature in Malaysia, was established after its first inaugural meeting at Bintulu on 8th September 1867. Its first 21-member Sarawak General Council, headed by Rajah Charles Brooke, consisted of six of Brooke’s officers and 16 local community leaders. In 1903, the General Council was renamed Council Negri. In 1941, Brooke’s son, Vyner, established a written constitution known as the Constitution Order in Council during the 100th anniversary celebration of the Brookes’ rule in Sarawak. As a result, the Council Negri membership numbers were increased to 24. Instead of Vyner Brookes (in his role as Rajah) the Chief Secretary was appointed to preside over the Council Negri. In 1963, the Council Negri’s membership increased to 42. Since then, it rose incrementally to 48 in 1968, 56 in 1989, 62 in 1996 and 71 in 2006. In 1976, the Council Negri was renamed the Dewan Undangan Negeri (DUN). Chief Minister’s Department located at Wisma Bapa Malaysia. The building was officiated on 17 August 1976 and taking the name of the first Prime Minister of Malaysia, Tunku Abdul Rahman Putra Al Haj as the “Father of Independence”. Besides the Chief Minister’s Office, the building also accommodates two Deputy Chief Ministers, young ministers, and State high ranking officers such as the State Secretary, State Finance Secretary, State Attorney General, and directors from various units and departments under the supervisions of Chief Minister Department.